Genome-wide identification, expression profiling, and functional analysis of ammonium transporter 2 (AMT2) gene family in cassava (Manihot esculenta crantz) - Xia, Jinze; Wang, Yu; Zhang, Tingting; Pan, Chengcai; Ji, Yiyin; Zhou, Yang; Jiang, Xingyu (Frontiers in Genetics, 2023)
Nitrogen (N), absorbed primarily as ammonium (NH4+) from soil by plant, is a necessary macronutrient in plant growth and development. Ammonium transporter (AMT) plays a vital role in the absorption and transport of ammonium (NH4+). Herein, seven AMT2-type genes (MeAMT2.1-2.7) were identified in cassava (Manihot esculenta), and their characteristics, expression patterns and functions were investigated. These MeAMT2 genes were distributed on 6 chromosomes and included two segmental duplication events (MeAMT2.2/MeAMT2.4 and MeAMT2.3/MeAMT2.5). Based on their amino acid sequences, seven MeAMT2 were further divided into four subgroups, and each subgroup contained similar motif constitution and protein structure. Synteny analysis showed that two and four MeAMT2 genes in cassava were collinear with those in the Arabidopsis and soybean genomes, respectively. Sixteen types of cis-elements were identified in the MeAMT2 promoters, and they were related to light-, hormone-, stress-, and plant growth and development-responsive elements, respectively. Most of the MeAMT2 genes displayed tissue-specific expression patterns according to the public RNA-seq data, of them, three MeAMT2 (MeAMT2.3, MeAMT2.5, and MeATM2.6) expressions were up-regulated under ammonium deficiency. Complementation experiments showed that yeast mutant strain TM31019b transformed with MeAMT2.3, MeAMT2.5, or MeATM2.6 grew better than untransgenic yeast cells under ammonium deficiency, suggesting that MeAMT2.3, MeAMT2.5, and MeATM2.6 might be the main contributors in response to ammonium deficiency in cassava. Therefore, this study provides a basis for further study of nitrogen efficient utilization in cassava.